2020
DOI: 10.1186/s13287-020-01886-2
|View full text |Cite
|
Sign up to set email alerts
|

Controlling stem cell fate using cold atmospheric plasma

Abstract: The stem cell is the foundation of regenerative medicine and tissue engineering. Regulating specific stem cell fate, such as cell attachment, proliferation, differentiation, and even death, undergoes continuous development. Cold atmospheric plasma (CAP), the core technology of plasma medicine, is attracting tremendous attention due to its ability and versatility to manipulate various types of cells, including stem cells. Specifically, the direct and indirect applications of CAP in controlling cell fate are bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…The Piezobrush compact handheld plasma devices (Relyon Plasma GmbH, Regensburg, Germany), PZ2 and PZ3, were used throughout the experiments 7 . They are based on the CeraPlas component and piezoelectric direct discharge (PDD) technology, in which low input voltage is transformed to create high electric field density (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Piezobrush compact handheld plasma devices (Relyon Plasma GmbH, Regensburg, Germany), PZ2 and PZ3, were used throughout the experiments 7 . They are based on the CeraPlas component and piezoelectric direct discharge (PDD) technology, in which low input voltage is transformed to create high electric field density (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The Piezobrush compact handheld plasma devices (Relyon Plasma GmbH, Regensburg, Germany), PZ2 and PZ3, were used throughout the experiments. 7 They are based on the CeraPlas component and piezoelectric direct discharge (PDD) technology, in which low input voltage is transformed to create high electric field density (Figure 1). The piezoelectric radiofrequency (RF) plasma generator provides several advantages, such as a high ionization speed, an effective RONS generation rate, multigas ignition, low power consumption, and no magnetic fields.…”
Section: Plasma Setup and Cellular And Animal Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In regenerative medicine, NTAPP may allow a versatile range of applications involving the manipulation of various cell types and processes, including stem cell attachment, proliferation, differentiation, and even apoptosis [3]. Tan et al reported evidence of NTAPP improving stem cell attachment, proliferation, and differentiation [3].…”
Section: Introductionmentioning
confidence: 99%
“…In regenerative medicine, NTAPP may allow a versatile range of applications involving the manipulation of various cell types and processes, including stem cell attachment, proliferation, differentiation, and even apoptosis [3]. Tan et al reported evidence of NTAPP improving stem cell attachment, proliferation, and differentiation [3]. It activated proliferation of various mesoderm-derived human stem cells [4], and enhanced proliferation of adipose tissue-derived stem cells without affecting their stem cell properties [5].…”
Section: Introductionmentioning
confidence: 99%